PENINGKATAN KREATIVITAS ANAK MELALUI MODEL PEMBELAJARAN BEYOND CENTERS AND CIRCLE TIME (BCCT) - SUKIMAN, SUKIMAN (PPs UNJ, 2012)
This study aims to determine the increased of children creativity of drawing and playing with clay through learning model of Beyond Centers and Circle Time. The study involved seventeen children of kindergarten group B in the ECE Learning Center of Yarsi, Jakarta. Research carried out by using the method of action research spiral cycle model developed by Kemmis & Mc. Taggart and successfully completed in three cycles. Quantitative data collected through the performence of early assessment and assessment of each the end of the cycles of action. Quantitative data on the childs creativity score improvement was analyzed using descriptive statistics. The results show that: (1) the creativity of drawing between cycles has increased, which is an average score on the pre-action x1=49,84), the end of the first cycle x2=53,29), the end of the second cycle x3=55,12), and post-action x4=57,00); and (2) the creativity of playing with clay between cycles increased, which is an average score on the pre-action x5=39,69), the end of the first cycle x6=43,56), the end of the second cycle x7=45,41), and post-actionÂ x8=46,20).Keywords: creativity, kindergarten, beyond centers and circle time